Implementation Of Gamification Learning Methods Using the Wordwall Application to Improve Students' Higher-Order Thinking Skills - Siti Maysarah (Journal of General Education and Humanities, 2026)
The low level of Higher Order Thinking Skills (HOTS) among junior high school students, especially in mathematics, indicates the need for technology-based learning innovations to train higher-level thinking skills. The low level of Higher Order Thinking Skills (HOTS) among eighth-grade students at Harapan 3 Junior High School, which is still dominated by lower-level thinking skills, is a problem in mathematics learning. The purpose of this study was to determine the effect of implementing a gamification learning method, assisted by the Wordwall application, on improving HOTS among eighth-grade students at SMP Harapan 3. This study used a quantitative approach, a quasi-experimental design, and a pretest-posttest nonequivalent control group design. The research instrument was an essay test that had been validated and was reliable for measuring students' HOTS abilities in the aspects of analysis, evaluation, and creation. The data were analysed using the Shapiro-Wilk normality test and Levene's homogeneity-of-variance test to guide the selection of statistical analysis techniques. Because the data were not normally distributed, the difference analysis was performed using the Mann-Whitney U Test, a nonparametric test and N-Gain calculation. The results showed that Wordwall-assisted gamification learning was significantly more effective than conventional learning in improving students' HOTS abilities.